(untitled) (Research, Society and Development, 2021)
Health promotion is defined as the process of training a population to act improving their quality of life. The Brazilian National Oral Health Policy establishes that oral health care services must have a comprehensive care character, with a focus on health promotion and disease prevention. This study aimed to describe the health promotion actions carried out by the Oral Health Strategy in municipalities in southern Brazil. This is a study carried out in seven municipalities in States of Santa Catarina and Rio Grande do Sul. In all 49 dentists who work in the Primary Care network participated. A semi-structured questionnaire was applied with questions aimed at identifying the health promotion actions developed by the participants. Among the actions, training to specific groups prevailed (79.6%). It was observed integration between the actions of dental surgeons and other professionals in primary care.